DAPATKAH NILAI PRESTASI BELAJAR DI SMA DIPERGUNAKAN UNTUK MERAMALKAN NILAI PRESTASI BELAJAR DI PERGURUAN TINGGI - Yusuf Siregar (Jurakunman (Jurnal Akuntansi dan Manajemen), 2019)
This studi is aimed to determine whether the student achievement in SMA is reliable to predict their achievement in the College. The study have been done in STIE Surya Nusantara Pematangsiantar. The sample consist of 61 students, the population is 153 students. The new students from 1st semester does not included in this study because their academic certificate (STTB) and grade do not available yet in the registrar office. The result of the study for 1st group r = 0,1264; the 2nd group r = 0,3655; the 3rd group r = 0,286. Based on the study, there are weak and positif corelations between student achievement in senior high school and achievement in the college. The conclusion, the correlation is positive toward the achievement of GPA in college eventhough it is weak (r = 0,12; 0,36, and 0,28).